Controlled release of dexamethasone in PCL/silk fibroin/ascorbic acid nanoparticles for the initiation of adipose derived stem cells into osteogenesis - Gandhimathi, Chinnasamy (2016)
Mimicking hybrid extracellular matrix is one of the major challenges in bone tissue engineering. Biocomposite micro/nanoparticle of polycaprolactone (PCL), silk fibroin (SF), ascorbic acid (AA) and dexamethasone (DM) were fabricated by the electrospraying methods in order to generate an improved osteogenic environment for the proliferation and differentiation of adipose derived stem cells (ADSCs) into osteogenesis. Fabricated electrosprayed micro/nanoparticle was characterized for particle morphology, hydrophilicity, porosity and FTIR analysis for bone tissue regeneration. FESEM micrographs of the nanoparticles revealed porous, fibreless, uniform particles with particle diameter in the range of 720 ± 1.8 nm - 3.5 ± 4.2 µm. The drug release profile indicates that the sustained release of dexamethasone up to 10 days and degradation of nanoparticles around 13-20% after 60 days. ADSCs were cultured on these nanoparticles and were induced to undergo osteogenic differentiation in the presence of AA/DM. The cells morphology, proliferation and interaction were analysed by CMFDA dye extraction method, MTS assay and FESEM analysis respectively.ADSCs differentiation into osteogenesis was confirmed using alkaline phosphatase activity and mineralisation by Alizarin Red staining. The significance of AA and DM biomolecules initiates particular biological functions for the proliferation of ADSCs and differentiation into osteogenic lineages. The obtained results proved that the biocomposite PCL/SF/AA/DM micro/nanoparticle stimulated osteogenic differentiation and mineralisation of ADSCs for bone tissue regeneration.